The Dynamics of the Monetary Policy Volatility: A Spectrum-vector Autoregressive Approach - Moosavi Mohseni, Reza; Cao, Jiling; Zhang, Wenjun (International Journal of Economics and Financial Issues, 2019)
This paper investigates the impact of the international and domestic volatility of monetary policy shocks on the economy of New Zealand using the spectrum-SVAR approach. We enrich the SVAR model by using time-varying global and domestic volatility as endogenous variables. The results show that although monetary policy shocks have transient effect on the real economy impact of the volatility of monetary policy shocks on the real part of the economy is permanent and relatively significant. Findings reveal that the supply shocks have a permanent impact on the supply side of New Zealand. The results of variance decomposition also show that New Zealand heavily depends on international shocks, so these types of shock can have a permanent impact on the local economy. Finally, the results of periodogram and significant pass filter suggest at least two deterministic cycles in the volatility of monetary policy. Keywords: Spectral Analysis; Volatility of Monetary Policy; Structural VAR JEL Classifications: C32; C54; E52 DOI: https://doi.org/10.32479/ijefi.6749